Perancangan Sistem Inventory Spare Part Elektronik Berbasis Web Application (Studi Kasus: Maspion Service Center) - Luqman Abdur Rahman Malik; Rizki Kamelia; Firman Noor Hasan (Jurnal Teknik Informatika dan Komputer, 2023)
This study aims to simplify and speed up the making of spare part stock reports at the Maspion Service Center and to avoid the risk of data recording errors that occur during spare part stock data collection. The method used in this research is the waterfall method. The researcher aims to design a spare part stock inventory system at the Maspion Service Center in order to simplify and speed up the making of spare part stock reports at the Maspion Service Center without recording in the ledger. The testing method used by the researcher is the Blackbox testing method. The results obtained in the design of this system are proven to be able to avoid the risk of data recording errors that occur during data collection of spare part stock, with the existence of a spare part stock database that is not possible with the same type of spare part twice